2002
DOI: 10.1542/peds.109.2.e35
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Impact of Growth Hormone Treatment for Children and Adolescents With Prader-Willi Syndrome: A 2-Year, Controlled Study

Abstract: ABSTRACT. Introduction. Prader-Willi syndrome (PWS) is characterized by obesity, hypotonia, hypogonadism, hyperphagia, short stature, and a neurobehavioral profile that includes cognitive deficits, learning problems, and behavioral difficulties that increase in both quantity and severity over time. PWS results from an alteration in the molecular composition of a critical region of C#15q. Morbid obesity resulting from hyperphagia is amplified by decreased energy expenditure and reduced physical activity. The hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 26 publications
4
51
0
5
Order By: Relevance
“…However, it has been demonstrated that in PWS patients GH treatment (GHT) reduces fat mass and increases body free fat mass percentage [4,12,13,14], improves respiratory muscle strength and endurance [15], and increases resting metabolic rate as well as physical strength and agility[14]. Changes in behaviour have also been observed [16] and beneficial effects on growth velocity have been demonstrated in many studies [6,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that in PWS patients GH treatment (GHT) reduces fat mass and increases body free fat mass percentage [4,12,13,14], improves respiratory muscle strength and endurance [15], and increases resting metabolic rate as well as physical strength and agility[14]. Changes in behaviour have also been observed [16] and beneficial effects on growth velocity have been demonstrated in many studies [6,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Eiholzer and colleagues 106 found, through parent reporting, that GH treatment increased alertness and enjoyment in physical activity in children with PWS. Similarly, Whitman and colleagues 122 found a significant reduction of depressive symptoms from baseline to time 1 (12 months) and retained at 24 months among those treated with GH. However, for children aged 11 years and younger, a significant increase in attention-deficit/hyperactivity symptoms was observed.…”
Section: Growth Hormonementioning
confidence: 78%
“…In the first year of life, reduced growth velocity may not be readily identified, but both controlled clinical trials 22 There is mounting evidence from controlled clinical trials that GH therapy in children improves linear growth, lean mass and lean-to-fat ratio, 27 and respiratory drive, 26,28 and there has been suggestion of beneficial effects on bone density 27,29 and possible stabilization of behavior decline. 30 Studies are in progress to evaluate the use of GH in adults with PWS. 31 However, there is nothing to suggest that endogenous GH insufficiency improves in later life; therefore, it is reasonable to consider continuing therapy into adulthood.…”
Section: Endocrine Considerations and Recombinant Human Growth Hormonementioning
confidence: 99%